EXPERIMENTAL STUDY FOR THE INTERACTION CURVES OF CFST COLUMNS SUBJECTED TO A STATIC CENTRIC OR ECCENTRIC LOADS - Alaa Hadi Hameed Hassoon (University of Thi-Qar Journal, 2019)
An experimental study on composite columns of square and circular steel hollow sections filled with normal concrete has been held in this paper. The concrete used in this study have two different compressive strength with mixing ratios of (1:2:4) and (1:1.5:3); the compressive strength of concrete were (22.9 MPa) and (31.8 MPa) respectively. Square steel hollow sections of (7.5×7.5 cm) and 2 mm thickness used with a yield stress of (352 MPa) while the circular hollow sections have (7.5 cm) diameter and 2 mm thickness with a yield strength of (327 MPa). Samples tested under the effect of concentric and eccentric axial loads with one case in which the column tested horizontally as a beam to evaluate the maximum bending resistance. The interaction curves for both shapes of columns and for two different concrete compressive strength are presented with a simple analysis for the pattern of failure in columns for each case of loading and for each type. The results show that the increase in compression strength of concrete provides more capacity for the composite columns in axial loading more than bending due to the confinement, and the failure in columns with square cross-sections are different from those which have circular cross-sectional area.